2012
DOI: 10.1503/cmaj.111758
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of patients, family caregivers and physicians about the use of opioids for refractory dyspnea in advanced chronic obstructive pulmonary disease

Abstract: Background: A recent national practice guideline recommends the use of opioids for the treatment of refractory dyspnea in patients with advanced chronic obstructive pulmonary disease (COPD). We conducted two qualitative studies to explore the experiences of patients and family caregivers with opioids for refractory COPD-related dyspnea and the perspectives and attitudes of physicians toward opioids in this context. Methods: Patients (n = 8; 5 men, 3 women), their caregivers (n = 12; 5 men, 7 women) and physici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
61
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 43 publications
3
61
1
Order By: Relevance
“…Nevertheless, long-held fears of further depressing respiration continue to limit more widespread acceptance by physicians [35] despite recommendations for their use in several recent professional society statements and/or clinical practice guidelines [20,36,37]. ualitative studies indicate e cacy and acceptability from patient and caregiver perspectives [35].…”
Section: Opioidsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, long-held fears of further depressing respiration continue to limit more widespread acceptance by physicians [35] despite recommendations for their use in several recent professional society statements and/or clinical practice guidelines [20,36,37]. ualitative studies indicate e cacy and acceptability from patient and caregiver perspectives [35].…”
Section: Opioidsmentioning
confidence: 99%
“…ualitative studies indicate e cacy and acceptability from patient and caregiver perspectives [35]. In contrast, physicians from general practice, internal medicine, palliative care and respirology suggested that lack of education and knowledge concerning opioids were among the greatest barriers to opioid use in advanced COPD [35]. ey also worried about possible censure for prescribing opioids in this context.…”
Section: Opioidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although guidelines recommend opioids in palliating dyspnea, there is still a hesitance among practitioners in using these agents. Recent work by Rocker et al 35 has shown that there is lack of connection between practitioners' experience and comfort with opioids vs. patients' experiences, which are positive in those who are carefully selected and titrated. 35,36 Collaboration with palliative care should enhance treatment in this patient population.…”
Section: Referencesmentioning
confidence: 99%